Institutional factors and conditional conservatism in Malaysia: Does international financial reporting standards convergence matter? - Marzuk, M.; Abdul Wahab, Effiezal Aswadi (Elsevier, 2016)
We examine the impact of International Financial Reporting Standards (IFRS) convergence on conditional conservatism in Malaysia. In addition, we examine the influence of various institutional factors, namely, political connections, Bumiputras directors, family firms and richest-men connections on conservatism. Prior literature presents evidence of IFRS convergence on conservatism, but limited evidence exists on the role of institutional factors on conservatism. Using a sample of 1760 firm-year observations from 2004 to 2008, we provide evidence that IFRS enhances conservatism. Firms with Bumiputras directors and family firms are more conservative post-IFRS convergence, whereas the reverse behaviour results for firms with richest-men connections. We find no evidence of politically connected firms being more conservative post-IFRS convergence. Our study provides knowledge on the role of IFRS in conditional conservatism and the role of institutional factors in this relationship.